Chrysis mediadentata Linsenmaier 1951 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
14. Chrysis mediadentata Linsenmaier, 1951 Chrysis ignita var. mediadentata Linsenmaier 1951: 75. Lectotype ♂ (designated by Linsenmaier 1959: 157); Switzerland: Wallis (NMLS) (examined) ( Chrysis ignita group). Remarks. The species has been reported from Finland by Valkeila (1962: 64, as C. ignita mediadentata ), Valkeila et al. (1963: 40, as C. ignita mediadentata ), Silfverberg (1981: 61), Vikberg (1986b: 68) and Ranta (2012: 33), from Norway by Erlandsson (1971: 88), Artsdatabanken (2010) and Rosa & Soon (2012), and from Sweden by Erlandsson (1971: 88), Janzon (1983: 171), Nilsson (1991: 86) and Rosa & Soon 2012 (as doubtful). All checked specimens have turned out to be incorrectly determined. A large proportion of them belong to an unknown taxon, which is closely related to C. ignita and C. impressa (see Chrysis sp.), but many belong to other species of the ignita group. Apparently, the distribution of C. mediadentata does not reach the Nordic and Baltic countries in Europe. The closest confirmed record is from northern Germany (Jakobs & Kornmilch 2007). : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 53, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Linsenmaier, W. (1951) Die europaischen Chrysididen (Hymenoptera). Versuch einer naturlichen Ordnung mit Diagnosen. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 24, 1 - 110.", "Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Brucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32, 1 - 232.", "Valkeila, E. (1962) Eraiden lounaissuomalaisten luonnonhistoriallisten maakuntien (V, U, St ja EH) myrkkypistiaiset (Hymenoptera, Aculeata). Lounais-Hameen Luonto, 13, 63 - 73.", "Valkeila, E., Brander, T. & Kapyla, M. (1963) Lounais-Hameen myrkkypistiaisista, Aculeata (Hymenoptera). Lounais-Hameen Luonto, 14, 39 - 44.", "Silfverberg, H. (1981) Additions to the Finnish insect fauna during the years 1976 - 1980. Notulae Entomolgicae, 61, 45 - 61.", "Vikberg, V. (1986 b) A checklist of aculeate Hymenoptera of Finland (Hymenoptera, Apocrita Aculeata). Notulae Entomologicae, 66, 65 - 85.", "Ranta, Y. (2012) Palkaneen kultapistiaiset (Hymenoptera, Chrysididae). Diamina, 21, 30 - 35.", "Erlandsson, S. (1971) Catalogus Insectorum Sueciae XIX. Hymenoptera: Aculeata. Entomologisk Tidskrift, 22, 87 - 94.", "Artsdatabanken (2010) Nasjonal kunnskapskilde for biologisk mangfold [Database of Norway's fauna and flora.] Available from: http: // www. artsportalen. artsdatabanken. no / (accessed 1 November 2013)", "Rosa, P. & Soon, V. (2012) Fauna Europaea: Chrysididae. In: Mitroiu, M. - D. (Ed.), Fauna Europaea: Hymenoptera, version 2. 5. Available from http: // www. faunaeur. org (accessed 1 November 2013)", "Janzon, L. - A. (1983) Gaddsteklar och andra blombesokande insekter pa Olands Stora alvar. Entomologisk Tidskrift, 104, 169 - 182.", "Nilsson, G. E. (1991) The wasp and bee fauna of the Rido archipelago in Lake Malaren, Sweden (Hymenoptera, Aculeata). Entomologisk Tidskrift, 112, 79 - 92.", "Jakobs, H. - J. & Kornmilch, J. - C. (2007) Die Goldwespen Mecklenburg-Vorpommerns (Hymenoptera, Chrysididae). Entomologische Nachrichten und Berichte, 51, 73 - 93."]}